Relapsing dermatofibroma with satellitosis in a 3-month-old baby. - Garofalo, L.; Greco, I.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2007)
A case of relapsing dermatofibroma with satellitosis in a six-month-old boy is reported. It should be differentiated from dermatofibrosarcoma protuberans.